Seafloor Density Contrast Derived From Gravity and Shipborne Depth Observations: A Case Study in a Local Area of Atlantic Ocean - Wan, Xiaoyun; Han, Weipeng; Ran, Jiangjun; Ma, Wenjie; Annan, Richard Fiifi; Li, Bing (Frontiers in Earth Science, 2021)
Marine gravity data from altimetry satellites are often used to derive bathymetry; however, the seafloor density contrast must be known. Therefore, if the ocean water depths are known, the density contrast can be derived. This study experimented the total least squares algorithm to derive seafloor density contrast using satellite derived gravity and shipborne depth observations. Numerical tests are conducted in a local area of the Atlantic Ocean, i.e., 34°∼32°W, 3.5°∼4.5°N, and the derived results are compared with CRUST1.0 values. The results show that large differences exist if the gravity and shipborne depth data are used directly, with mean difference exceeding 0.4 g/cm3. However, with a band-pass filtering applied to the gravity and shipborne depths to ensure a high correlation between the two data sets, the differences between the derived results and those of CRUST1.0 are reduced largely and the mean difference is smaller than 0.12 g/cm3. Since the spatial resolution of CRUST1.0 is not high and in many ocean areas the shipborne depths and gravity anomalies are much denser, the method of this study can be an alternative method for providing seafloor density variation information.